National practice patterns and direct medical costs for prostate cancer in Korea across a 10 year period: a nationwide population-based study using a national health insurance database - Ho Won Kang; Seok-Joong Yun; Jae Il Chung; Hoon Choi; Jae Heon Kim; Ho Song Yu; Yun-Sok Ha; In-Chang Cho; Hyung Joon Kim; Hyun Chul Chung; Jun Sung Koh; Wun-Jae Kim; et al. (BMC, 2019)
Abstract Background A complete enumeration study was conducted to evaluate trends in national practice patterns and direct medical costs for prostate cancer (PCa) in Korea over a 10-year retrospective period using data from the Korean National Health Insurance Service. Methods Reimbursement records for 874,924 patients diagnosed between 2002 and 2014 with primary PCa according to the International Classification of Disease (ICD) 10th revision code C61 were accessed. To assess direct medical costs for patients newly diagnosed after 2005, data from 68,596 patients managed between January 2005 and 31 December 2014 were evaluated. Results From 2005 to 2014, the total number of PCa patients showed a 2.6-fold increase. Surgery and androgen deprivation therapy were the most common first-line treatment, alone or within the context of combined therapy. Surgery as a monotherapy was performed in 23.5% of patients in 2005, and in 39.4% of patients in 2014. From 2008, the rate of robot-assisted RP rose sharply, showing a similar rate to open RP in 2014. Average total treatment costs in the 12 months post-diagnosis were around 10 million Korean won. Average annual treatment costs thereafter were around 5 million Korean won. Out-of-pocket expenditure was highest in the first year post-diagnosis, and ranged from 12 to 17% thereafter. Conclusions Between 2005 and 2014, a substantial change was observed in the national practice pattern for PCa in Korea. The present data provide a reliable overview of treatment patterns and medical costs for PCa in Korea.